RANCANG BANGUN SISTEM INVENTORY DAN KASIR BERBASIS WEB PADA JALAKOTEK ASEP (Studi Kasus: Toko Jalakotek Asep) - Fauzan Faturahman Azkia; Ardi Mardiana (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The effective management of inventory is a critical aspect of any business, as it directly influences operational efficiency, cost control, and customer satisfaction. In this study, we present the design and implementation of a comprehensive Inventory Management System (IMS) aimed at optimizing inventory control and streamlining the inventory-related processes for small and medium-sized enterprises (SMEs). The system is developed using a combination of modern technologies, including a web-based front-end for easy accessibility and a robust database to store inventory-related information securely. The backend utilizes algorithms to predict demand patterns, ensuring optimized stock levels to prevent stockouts and overstocking. The results indicate that the implementation of the IMS significantly improves inventory management efficiency, reduces carrying costs, and enhances inventory accuracy by minimizing manual errors. The streamlined processes lead to faster order fulfillment and improved customer satisfaction.